1993
DOI: 10.1002/hc.520040220
|View full text |Cite
|
Sign up to set email alerts
|

α‐Trifluoromethyl substituted α‐aminoacids and α‐hydroxyacids with organometallic moieties in the side chain [1,2]

Abstract: Several strategies for the synthesis of a-trifluoromethyl substituted a-aminoacids and a-hydroxyacids with organometallic moieties in the side chain are described. The preparative potential of organometallic substituents (organosilicon, organotin, and organocobalt moieties) offers a convenient methodology for the synthesis of highly functionalized a-aminoacid and a-hydroxyacid derivatives.a-Trifluoromethyl substituted a-aminoacids play an important role as suicide inhibitors of pyridoxal phosphate dependent en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…To extend the range of biomolecules containing a dicobalthexacarbonyl unit, we embarked on a program to synthesize simple amino acids, small peptides, and peptide nucleic acid monomers (PNA) with the Co 2 (CO) 6 moiety, as previously undertaken by our group with ferrocene or/and platinum(0) complexes . To the best of our knowledge, only Burger et al reported a α-trifluormethyl substituted α-ethinyl-amino acid cobalt complex, which was then reacted, under Pauson-Khand conditions, to give the cyclopentenone substituted α-trifluoromethyl amino acid derivative …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend the range of biomolecules containing a dicobalthexacarbonyl unit, we embarked on a program to synthesize simple amino acids, small peptides, and peptide nucleic acid monomers (PNA) with the Co 2 (CO) 6 moiety, as previously undertaken by our group with ferrocene or/and platinum(0) complexes . To the best of our knowledge, only Burger et al reported a α-trifluormethyl substituted α-ethinyl-amino acid cobalt complex, which was then reacted, under Pauson-Khand conditions, to give the cyclopentenone substituted α-trifluoromethyl amino acid derivative …”
Section: Introductionmentioning
confidence: 99%
“…42 To the best of our knowledge, only Burger et al reported a R-trifluormethyl substituted R-ethinyl-amino acid cobalt complex, which was then reacted, under Pauson-Khand conditions, to give the cyclopentenone substituted R-trifluoromethyl amino acid derivative. 43 In this paper, we report our initial results on the preparation of dicobalthexacarbonyl derivatives of the amino acids phenylalanine (Phe) and methionine (Met), as well as the first crystallographic characterization of a dicobalthexacarbonyl amino acid derivative. Using solid phase peptide synthesis (SPPS) techniques, the formation of two dicobalthexacarbonyl derivatives of the neuropeptide Enkephalin (Enk) is described.…”
Section: Introductionmentioning
confidence: 99%
“…The most general approach to C a,a -disubstituted fluorinated amino acids is based on the addition of carbon nucleophiles to the CN double bond of N-substituted imines of alkyl trifluoroand difluoropyruvate. [63][64][65][66] Grignard reagents are the nucleophiles of choice because they tolerate certain functional groups, including CC double, CC triple bonds, and metallorganic moieties like organosilicon, organotin, and organoco-balt substructures, 67,68 which can be reacted further to give multifunctional aTfm and aDfm amino acids. 69,70 Moreover, this strategy allows the incorporation of the Boc-and Z-group for orthogonal protection.…”
Section: Atfm and Adfm Amino Acids Via Introduction Of The Alkyl Subs...mentioning
confidence: 99%
“…We have first developed an effective protocol for the preparation of new trifluoromethyl-containing 1,6-and 1,7-azadiynes starting from readily available imines of methyltrifluoropyruvate. The synthetic sequence includes two simple stages: (i) the addition of sodium acetylenide 16 or allenylmagnesium bromide 17 to electrophilic imines 1 takes place under mild conditions to give the corresponding a-alkynyl derivatives 2 and 3 (Scheme 1); (ii) the Nalkylation of alkynyl-substituted amino esters with propargyl bromide, after deprotonation with sodium hydride in DMF, affords azadiynes 4 and 5 with acceptable yields (Table 1).…”
mentioning
confidence: 99%